Pengaruh Intellectual Capital, Firm Size, Liquidity Dan Capital Structure Terhadap Firm Performance - Aurellia Clarissa Sutandi, Sofia Prima Dewi (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to examine the effect of intellectual capital, firm size, liquidity, and capital structure on firm performance of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. This research uses secondary data in the form of financial statements which was tested using Eviews Software version 10.0 SV. This research uses 82 manufacturing companies that have been selected through a purposive sampling method with a total of 246 data for three years. The results of the research showed that intellectual capital has positive effects to the firm performance and capital structure has negative effects to the firm performance, while firm size and liquidity have no positive effect to the firm performance. The implication of this research is that companies need to maintain the quality of their resources to create a competitive advantage and companies need to pay attention to their capital loans to keep up the performance.